Sustainable Development. Systematization of Subject Domain - Danilina, Ya. V.; Gerbina, T. V. (Scientific and technical information processing, 2024)
— Sustainable development (SD) has become one of the single-option requirements of our times. The concept of SD is a new, synthetic field of knowledge in formation. This concept has been the result of research in various fields of knowledge about nature, society, and economy. The novelty and interdisciplinary essence of SD determine the need to systematize this subject domain to develop a more complete and accurate representation of it, as well as improving the relevance of information search. The aim of this study is to systemize the information from the Database (DB) of the All-Russian Institute for Scientific and Technical Information of the Russian Academy of Sciences (VINITI) concerning the subject domain of SD and identify the relevant subject-specific fragment. The formative timeline of the concept of SD and its current state are presented. A review of the world’s main scientific information resources aggregating the scientific information on this subject is provided. An attempt has been made to systemize this scientific and technical information by branches of knowledge with three zero levels. These are the environmental, the economic, and the social problems of SD, and they were initially laid down as basic in the SD concept. This approach has allowed identifying about 600 branches, each of which is a separate scientific discipline in the context of SD and, building the most complete map of the subject area (in the context of the VINITI DB). This map is structured as a hierarchical tree.